LATE PRESENTING CONGENITAL DIAPHRAGMATIC HERNIA IN A 4-YEAR-OLD CHILD - Kirovski, Ilija; Nonkulovski, Danilo (Journal of Morphological Sciences, 2023)
The majority of congenital diaphragmatic hernia (CDH) are diagnosed antenatally, immediately after birth or in the neonatal period. We report case of 4-year-old child who presented with recurrent wheezing and was diagnosed to have late presenting CDH. A 4-year-old girl was admitted to the hospital with a 5-days history of increasing shortness of breath and cough. The child had normal bird history and has enjoyed relatively good health till 3 years of age. Her medical history over the last year revealed that she had 4 episodes of wheezing variously treated with inhaled bronchodilators, steroids and antibiotics. On physical examination she was in mild respiratory distress with bilateral wheezing. The x-ray showed an unusual appearance of the chest with air-filled bowel loops. A barium X-ray examination of the gastrointestinal tract confirmed the diagnosis of CDH. The hernial contents were reduced back into the abdominal cavity and surgical repair of the diaphragmatic defect was done. Late presenting CDH can be misdiagnosed and lead to delayed treatment. It should be suspected in children presenting with recurrent respiratory symptoms.  When the diagnosis is confirmed, the treatment of choice is surgical intervention. Clinical awareness, early diagnosis and operative treatment can lead to good outcomes. Key words : Congenital diaphragmatic hernia, child, wheezing.   https://doi.org/10.55302/JMS2361132k